Use of Ammonia Salts in Selective Copper Extraction from Tailings - Turan, M. Deniz; Orhan, Ramazan; Turan, Mucevher; Nizamoglu, Hasan (Springer Heidelberg, 2020)
Tailings (flotation waste) that is formed during copper production may be considered in the class of valuable wastes due to the amount of copper it contains. Owing to the decreasing grade values in copper ores, utilization of wastes such as tailings that carry certain amounts of copper as secondary sources has become a necessity in both the economic and environmental sense. This study investigated the usage conditions of five different ammonia salts as leaching reactants for the purpose of selective extraction of copper from tailings. For this purpose, the effects of parameters such as leaching temperature and leaching time were examined at different concentrations of ammonium hydroxide, ammonium carbonate, ammonium nitrate, ammonium chloride, and ammonium persulfate. The copper extraction efficiency in the case of using the aforementioned salts by themselves were listed as (NH4)(2)CO3 (73%) > (NH4)(2)S2O8 (69%) > NH4OH (64%) > NH4Cl (42%) > NH4NO3 (40%). The highest copper extraction efficiency was obtained in the leaching process that was conducted with the solutions obtained by mixing ammonia salts in the best conditions. Accordingly, as a result of 6 h of leaching at 30 degrees C in the presence of 22.5% NH4OH and 100 g/L (NH4)(2)S2O8, 91.47% of the copper was transferred into the solution, while iron was not transferred. The obtained results showed that copper could be selectively recovered from tailings.
Keywords: Copper; Extraction; Tailings; Leaching; Ammonia salts